(untitled) (Journal of Universal Science Research, 2023)
The article provides detailed information about the life of Toni Morrison and his work. At the same time, Toni Morrison describes the period of writing of the works and the period-related aspects of the works. Toni Morrison’s views on twentieth-century culture, its development, and radical democracy are highlighted. Toni Morrison’s views on the developmental stages of critical realism are also cited. Details of what Toni Morrison did during his lifetime are also provided